Colonial Australian women poets : political voice and feminist traditions - Hansord, Katie (Anthem studies in Australian literature and culture, 2021)
This book considers the political and feminist significance of non-canonical women poets, particularly those who were writing in newspapers and periodicals, in colonial Australia.